The least number of n-periodic points on tori can be realized by a smooth map - Jezierski, Jerzy (Topological Methods in Nonlinear Analysis, 2016)
We give an algebraic proof of the Theorem of Cheng Ye You that the least number of $n$-periodic points, in the continuous homotopy class of a self-map of a~torus, can be realized by a smooth map.